THE INFLUENCE OF ONLINE CUSTOMER REVIEWS AND CUSTOMER TRUST ON ROOM PURCHASE DECISIONS AT ASTON NAGOYA CITY HOTEL BATAM - Haifa Nafisah (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the influence of Online Customer Reviews and Customer Trust on Room Purchase Decisions at Aston Nagoya City Hotel Batam. The study employed a quantitative method with a causal associative approach. Data were collected through questionnaires distributed to 130 respondents selected using a purposive sampling technique. The data were analyzed using multiple linear regression analysis with the assistance of SPSS version 27. The results indicate that the Online Customer Review variable obtained a mean score of 4.115, Customer Trust obtained a mean score of 4.145, and Room Purchase Decision obtained a mean score of 4.177, all of which were categorized as good. The hypothesis testing results reveal that Online Customer Reviews and Customer Trust have a positive and significant effect on Room Purchase Decisions, both partially and simultaneously. The Adjusted R² value of 0.557 indicates that the two independent variables explain 55.7% of the variation in Room Purchase Decisions, while the remaining 44.3% is influenced by other factors not examined in this study. The findings are expected to provide valuable insights for hotel management in improving service quality, effectively managing customer reviews, and strengthening customer trust to enhance room purchase decisions.